Principles of economics - Case, Karl E.; Fair, Ray C. (Prentice Hall, 1999)
Provides an introduction to economics, presenting various points of theory through stories, graphs, and equations, in a pedagogical tool that accommodates the students' varied styles of learning. This work also offers a supplements package to keep students motivated throughout the course.